2009
DOI: 10.1007/s10726-009-9181-y
|View full text |Cite
|
Sign up to set email alerts
|

Negotiator Satisfaction in NSS-Facilitated Negotiation

Abstract: Negotiator satisfaction plays an important role in the adoption and diffusion of Negotiation Support Systems (NSS). There is little knowledge about what factors shape the negotiator satisfaction in the NSS context. In this study, we investigated this factor from the perspectives of negotiator and end-user of NSS. We proposed a research model of negotiator satisfaction by incorporating negotiation outcomes and negotiator perception of the system and negotiation process. The empirical findings with 116 data poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 69 publications
0
10
0
1
Order By: Relevance
“…This is consistent with Remus' [24] findings in which individuals who are provided outcome feedback (via alternative solution data provided by the table data) are able to make more consistent, satisfactory decisions. In other words, although elaborate technologies designed to automate the majority of the negotiation process exist, negotiators seek more control and consistency over the negotiation process [30]. Our study finds that even simple technologies (like the one employed in this study) may also contribute to greater negotiator satisfactionperhaps because of the straightforward, negotiator-controlled payoff data they yield.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This is consistent with Remus' [24] findings in which individuals who are provided outcome feedback (via alternative solution data provided by the table data) are able to make more consistent, satisfactory decisions. In other words, although elaborate technologies designed to automate the majority of the negotiation process exist, negotiators seek more control and consistency over the negotiation process [30]. Our study finds that even simple technologies (like the one employed in this study) may also contribute to greater negotiator satisfactionperhaps because of the straightforward, negotiator-controlled payoff data they yield.…”
Section: Discussionmentioning
confidence: 68%
“…No special training or experience was needed to use the software, unlike other, more complicated negotiation support systems (NSS). Although the sophisticated software systems found in most NSS can be useful in reducing the time and effort required to prepare for a negotiation, Wang, Lim and Guo [30] found that most negotiators valued control over the process and outcomes. In fact, negotiators in their study tended to ignore suggestions made by the sophisticated software in favor of their own solutions, and they reported more satisfaction when allowed more individual control throughout the negotiation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of fairness on negotiator satisfaction was confirmed in the context of Negotiation Support Systems (NSS)facilitated negotiation. It revealed that perceived fairness, next to the the degree of perceived collaborative atmosphere and perceived control, was a better predictor of negotiator satisfaction than negotiation outcomes [43]. Nevertheless, the degree of satisfaction with the outcome enhances the motivation to sustain the relationship and therefore has a positive effect on the willingness to renegotiate [37].…”
Section: Effect Of Dominance On Negotiation Outcomesmentioning
confidence: 99%
“…Asimismo respecto a la percepción del mejoramiento del proceso de negociación internacional, autores como Swaab, Postmes, Neijens, Kiers y Dumay (2002) realizan un estudio donde sugieren que las TIC permiten alcanzar acuerdos de forma eficiente, generando mayor satisfacción en los negociadores, en especial porque estos encuentran confirmaciones objetivas de la contraparte, y perciben equidad y control en una atmosfera colaborativa (Wang, Lim y Guo, 2010).…”
Section: Relación E Impacto De Las Tic En La Efectividad De La Negociunclassified